Convalescent plasma therapy for coronavirus infection: experience from MERS and application in COVID-19 - Jaffar A. Al-Tawfiq; Yaseen Arabi (Taylor & Francis Group, 2020)
The emergence of the COVID-19 pandemic has resulted in a very large number of infections and high number of mortality. There is no specific therapeutic options that are approved for clinical use. Administration of convalescent plasma as a possible therapy was used in the case of viral pneumonia including SARS and influenza. There have been multiple studies of COVID-19 patients utilizing convalescent plasma. These studies employed different dosage levels and different regiments, were observational and lacked control arms, and had variable outcomes. Two of these studies used plasma with anti-SARS-CoV-2 titers of >1:640 to >1:1000. A recent randomized controlled clinical trial showed no benefit of convalescent plasma in patients with severe diseases. However, the study was terminated early and thus further clinical trials are needed to show efficacy in patients with COVID-19 infection.